Instruments to assess gait in individuals with multiple sclerosis: a systematic review - Jesus, Maria Margarida de (2023)
Background: Gait impairment is considered a significant cause of disability and is a clinical feature of Multiple Sclerosis. For this reason, their regular assessment is essential for better management and treatment and to evaluate the effectiveness of rehabilitation. Objective: This study aims to know what instruments are available in the literature to assess gait in patients diagnosed with MS. Data Sources and Searches: A complete literature search was conducted in MEDLINE, Web of Science, Embase, and Scopus, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The study protocol was registered at the International Prospective Register of Systematic Reviews (PROSPERO). Study Selection: The authors selected studies written in English and representing validation of gait assessment tools exclusively for adults with a diagnosis of MS. Data Extraction and Quality Assessment: Two authors independently extracted the data for reliability, measurement error, validity, and assessed methodological quality using the COnsensus-based standards to select health Measurement Instruments (COSMIN). Data Synthesis and Analysis: All authors performed data synthesis to determine the level of evidence per measurement property per tool.